Population genetic evidence that basidiospores play an important role in the disease cycle of rice-infecting populations of Rhizoctonia solani AG-1 IA in Iran - Padasht-Dehkaei, F.; Ceresini, P. C. [UNESP]; Zala, M.; Okhovvat, S. M.; Nikkhah, M. J.; Mcdonald, B. A. (Wiley, 2013)
The fungus Rhizoctonia solani AG-1 IA causes sheath blight, one of the most important rice diseases worldwide. The first objective of this study was to analyse the genetic structure of R. solani AG-1 IA populations from three locations in the Iranian Caspian Sea rice agroecosystem. Three population samples of R. solani AG-1 IA isolates were obtained in 2006 from infected rice fields separated by 126-263km. Each field was sampled twice during the season: at the early booting stage and 45days later at the early mature grain stage. The genetic structure of these three populations was analysed using nine microsatellite loci. While the population genetic structure from Tonekabon and Amol indicated high gene flow, they were both differentiated from Rasht. The high gene flow between Tonekabon and Amol was probably due mainly to human-mediated movement of infested seeds. The second objective was to determine the importance of recombination. All three populations exhibited a mixed reproductive mode, including both sexual and asexual reproduction. No inbreeding was detected, suggesting that the pathogen is random mating. The third objective was to determine if genetic structure within a field changes over the course of a growing season. A decrease in the proportion of admixed genotypes from the early to the late season was detected. There was also a significant (P=0·002) increase in the proportion of loci under Hardy-Weinberg equilibrium. These two lines of evidence support the hypothesis that basidiospores can be a source of secondary inoculum. © 2012 BSPP.
Keywords: Gene flow; Genetic structure; Mixed reproductive mode; Recombination; Thanatephorus cucumeris; agricultural ecosystem; disease resistance; fungal disease; gene flow; genetic structure; growing season; mating behavior; population genetics; population structure; recombination; rice; spore; Iran; Fungi